Genetic variability of the domestic cat (Felis catus) in Magangué, Bolívar, Colombia - Pardo, Enrique (2016)
The aim of this study was to determine the genetic variability of populations of domestic cats (Felis catus) using genes that encode color, design and length of pelage in Magangué, Bolivar, Colombia. A total of 297 cats were phenotyped by direct observations made on tours through urban areas in Magangué, providing the phenotypic markers: Orange, Agouti, Tabby, Dilution, Long hair, Spotting white y Dominant white. Population genetic parameters were calculated: allele frequencies, genetic diversity, gene flow, Hardy-Weinberg equilibrium and genetic distance and phylogenetic relationships among cat populations were inferred. The non-agouti marker was the most frequent, while Tabby blotched and Dominant white gene had the lowest values. Most of the genetic diversity was found within populations and low among populations as well as high gene flow. An excess of heterozygotes was observed at the population level and there was no Hardy-Weinberg equilibrium. The populations are highly genetically related and was evidenced a possible natural and artificial selection of the Non-agouti and Spotting white markers.